Nondestructive Condition Assessment Techniques for the Ethylene-Propylene Rubber Cable. Issue 1 (2nd January 2017) - Meng, Xiaokai; Wang, Zhiqiang; Li, Guofeng
ABSTRACT: In order to analyze the aging of the active Ethylene-Propylene Rubber (EPR) cable, the dielectric dissipation factor (tan δ) was proposed as a nondestructive method of cable insulation condition assessment. Firstly, the EPR marine cable was investigated in this article, and the data of elongation at break retention rate (EAB%) after accelerated aging under different temperatures were used to fit by means of the optimized time-temperature shift factor. The endpoint judgment index of dielectric dissipation factor was deduced when EAB% reached to 50%. Secondly, the cable's lifetime calculated by tan δ was compared with the EAB% in order to confirm the accuracy of the method. The results show that the lifetime of tan δ is consistent with EAB% and provides a new method for the rapid evaluation of the EPR cable's remaining life.